Effects of heavy metals on cytotoxicity of snakehead fish (channa striata) in the domestic waste water canal - BUNDIT TENGJAROENKUL; LAMYAI NEERATANAPHAN (International Journal of Pharma and Bio Sciences, 2018)
This research aims to study water quality, heavy metal concentrations in water, sediment, and Channastriata; and the cytotoxicity of C. striata from a domestic waste water canal compared with a non-affected area. The heavy metal concentrations (Pb, Cd, Cr, Cu, Fe, Mn, Ni and Zn) in water, sediment and C. striata were analyzed by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES), and chromosomal aberrations were analyzed directly from kidney cells. The Ni concentration in the water was higher than the standard limits while other heavy metal concentrations in the sediment and C. striata were lower than the standard. The diploid chromosome number of C. striata was 2n=42 in samples taken frombothareas.Fivetypes of chromosomal aberrations of C. striata included Single Chromatid Break (SCB), Single Chromatid Gap (SCG), Centromere Gap (CG), Deletion (D) and Fragmentation (F) at both areas. In the 300 cells evaluated, 98 chromosomal aberrations were found in 59 cells and the percentage of chromosomal aberrations was 19.6%. The percentage of chromosomal aberrations of C. striata in the domestic waste water canal was higher than that in the non-affected area. The most common chromosomalaberration in C. striata samples from the domestic waste water canal was SCG.